Cells Dynamically Adapt to Surface Geometry by Remodeling Their Focal Adhesions and Actin Cytoskeleton - Dede Eren, Aysegul; Lucassen, Amy W. A.; Tuvshindorj, Urandelger; Truckenmüller, Roman; Giselbrecht, Stefan; Eren, E. Deniz; Tas, Mehmet Orhan; Sudarsanam, Phanikrishna; de Boer, Jan (Frontiers in Cell and Developmental Biology, 2022)
Cells probe their environment and adapt their shape accordingly via the organization of focal adhesions and the actin cytoskeleton. In an earlier publication, we described the relationship between cell shape and physiology e.g. shape-induced differentiation, metabolism, and proliferation in mesenchymal stem cells and tenocytes. In this study, we investigated how these cells organize their adhesive machinery over time when exposed to microfabricated surfaces of different topographies and adhesive island geometries. We further examined the reciprocal interaction between stress fiber and focal adhesion formation by pharmacological perturbations. Our results confirm the current literature that spatial organization of adhesive sites determines the ability to form focal adhesions and stress fibers. Therefore, cells on roughened surfaces have smaller focal adhesion and fewer stress fibers. Our results further highlight the importance of integrin-mediated adhesion in the adaptive properties of cells and provide clear links to the development of bioactive materials.